Драматургія світла в архітектурі сучасних театральних будівель - Яців, М. Б.; Yatsiv, M. B. (Видавництво Львівської політехніки, 2019)
Розглянуто архітектурно-конструктивні чинники формування світлового середовища в сучасних театральних будівлях; виявлено тенденції та особливості функціонування природного світла в просторі окремих типів театральних будівель та вплив архітектоніки будівель на характер світлового середовища інтер’єру.

Lighting is a major component of theatrical performance. It is capable of shaping the space, creating an emotional atmosphere and outlining the pace of the theatrical action. The role of light in theater architecture is important. Natural light, while remaining relatively unchanged, in all epochs determined the nature of the perception of architectural objects and environment, emphasized the light and color of the architectonics of buildings, influenced the dynamics of the perception of form, and was at the same time a determining factor in the generation of emotions associated with perception. In the historical theatrical buildings there was an atmosphere of pomp, modesty, enthusiasm. The viewer, who entered the interior space, fully felt the atmosphere of “seclusion” of the interior. Thick walls and a small number of windows, reliably shield the sun, street noise. There is virtually no visual communication with the urban environment. Visitors’ attention is focused on interior design and communication with other viewers before the performance and intermission. Changes in science, technology, construction methods, encourage the revision of aesthetic ideals and views in the organization of the light environment of theater buildings. By the way the light environment is organized, modern theater buildings can be divided into three large groups. The first will involve theatrical buildings with the traditional organization of the light environment - natural light enters the inner space in small portions, through the small number of light openings in the structure of the outer walls. The interior of the rooms is mostly illuminated by artificial light. Another group of theatrical buddies has a more active room for open space. We will enlighten the stereotypes with gardening: stained-glass windows, structurally welded constructions. The third group is presented with theatrical performances, styles and navigation, which can be seen through the appearance of the material. Behind the installation of the classifications, the middle of the five theatrical bells came to light: Podoli Theater in Kyiv (Ukraine), Shakespeare Theater in Gdansk (Poland), Opera House in Oslo (Norway), Theater in Guangzhou (China) and Concert Center in Reykjavik (Iceland). In these theatrical buildings, the main tendency in the organization of the light environment is the transition from closed space, with low light, to the maximum filling of the premises with natural light. Monumental opaque walls in traditional theater buildings are replaced by transparent walls of glass and metal, allowing natural light to penetrate into the farthest reaches of the theatrical space. Conclusion. Architects offer new spatial solutions for theatrical buildings, new spatial forms and design solutions in accordance with trends in architecture and design ideas. Today, light not only manifests an architectural form, but gives an emotional depth to the architectural space, it is a means of creating a figurative-associative-creative perception when, under the influence of the light image, in the imagination associations with the landscapes of nature or elements of anthropogenic object origin arise. Thanks to the use of extensive glazing and various artificial lighting, modern architecture reflects modern reality – the blurring of the boundaries between internal and external, real and virtual space. Natural light is gradually being replaced by artificial light, first in the form of electric lighting systems, then in the form of light technologies that create a new reality.
Dramaturgy of light in the architecture of modern theater buildings
Keywords: театральні будівлі; світлове середовище; театральний простір; природне і штучне світло; theater buildings; lighting environment; theatrical space; natural and artificial light; 725.8.01